Social Motivation in Autism Spectrum Disorder: A Mixed-Methods Exploration Using Eye-Tracking, Behavioral Tasks, Self- and Parent-Reports, and Qualitative Insights. - Li, Jiaxi; Shum, Kathy Kar-man (Autism: The International Journal of Research & Practice, 2026)
Social motivation diminishment is a core autism feature, yet prior research has been inconsistent, focusing on single dimensions and overlooking heterogeneity in motivational expressions among autistic individuals. This mixed-methods study compared social motivation in 104 individuals with autism (male: 74, M age = 18.55 years) and 192 non-autistic peers (male: 101, M age = 16.65 years), using eye-tracking and behavioral tasks, self-/parent-reports, and qualitative analysis of open-ended responses. Quantitative analyses revealed autistic participants had lower self-determined motivation, driven by reduced intrinsic motivation and identified regulation. Parent-report results corroborated lower perceived social motivation in the autistic group. The eye-tracking task showed decreased orientation to social stimuli, and behavioral task indicated reduced willingness to exert effort for social rewards, with no significant associations with age or autistic trait. Qualitative data highlighted that despite challenges, many autistic participants valued friendship and sought connection through shared activities, often preferring compact, stable social networks. The group-level quantitative findings align with social motivation theory but underscore heterogeneity, showing that diminished social motivation in autism may stem from contextual challenges rather than uniform amotivation. This study advances the understanding of social motivation dynamics, emphasizing the need for inclusive assessments that recognize diverse motivational expressions and prioritize subjective experiences. Social motivation refers to how much people want to engage with others, notice social cues, and seek connections. Researchers have long debated whether autistic people's social challenges stem from lower social motivation. However, past studies often focused on only one aspect of social motivation and ignored individual differences among autistic people. We recruited 104 autistic and 192 non-autistic adolescents and young adults. Participants and their caregivers completed questionnaires about social motivation from their own and caregivers' perspectives. We used two behavioral tasks to measure how much attention participants devoted to social content, and how willing they were to exert effort for social rewards. Open-ended questions captured autistic participants' perspectives on friendship dynamics, social inclusion, and the meaning of social connection. We found that autistic participants reported lower social motivation, a finding supported by parent reports. They spent less time looking at social content and exerted less effort to obtain social rewards than non-autistic peers. However, their open-ended responses showed that they sought social connection through shared activities, preferred small and stable social networks, and found joy and belonging in close friendships, despite challenges such as the strain of social interaction. Our results can help professionals avoid misinterpreting autistic people's social behaviors, and help families and peers recognize autistic individuals' expressions of social interest, reducing unfair judgments and promoting more respectful interactions. In addition, these findings support the development of assessments and social programs that reflect autistic perspectives.